2004
DOI: 10.1111/j.0300-9475.2004.01413.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Adhesion Molecule Expression on Endothelial Cells after Induction by Lipopolysaccharide‐Stimulated Whole Blood

Abstract: The relative contribution of the pro-inflammatory cytokines tumour necrosis factor (TNF)-a and interleukin (IL)-1b and the lipopolysaccharide (LPS)-induced pathways that result in endothelial activation during sepsis are not fully understood. We have examined the effects of plasma obtained from LPStreated human whole blood on the expression of E-selectin and intercellular adhesion molecule-1 (ICAM-1) on human endothelial cells. Stimulation of blood with 10 pg/ml of LPS is sufficient to produce plasma that indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…This is in line with previous studies demonstrating that plasma from E. coli-activated heparin anticoagulated whole blood (27) or conditioned medium with LPSactivated THP-1 cells, a monocytic cell line (28), caused ∼100-fold more potent activation of EC than did activating EC directly with the same concentration of E. coli or LPS. Thus, it seems that although E. coli can directly activate EC, this does not play a significant role due to the shear scale of leukocyte-induced activation.…”
Section: Discussionsupporting
confidence: 92%
“…This is in line with previous studies demonstrating that plasma from E. coli-activated heparin anticoagulated whole blood (27) or conditioned medium with LPSactivated THP-1 cells, a monocytic cell line (28), caused ∼100-fold more potent activation of EC than did activating EC directly with the same concentration of E. coli or LPS. Thus, it seems that although E. coli can directly activate EC, this does not play a significant role due to the shear scale of leukocyte-induced activation.…”
Section: Discussionsupporting
confidence: 92%
“…The present study identified that the expression of IL-8 was continuously high along with the severity of lung injury, and peaked following injection of LPS for 4 h. The results also indicated that increased IL-8 expression may promote the migration of a large number of PMNs from the peripheral blood to the lung tissue, and PMNs release toxic substances, such as MPO. In addition, IL-8 may activate PMNs and directly damage the lung tissue cells (27). …”
Section: Discussionmentioning
confidence: 99%
“…Plasma of the same donors was used throughout the experiments. Our previous study demonstrated that the response of HUVEC to plasma obtained from these donors was essentially similar [14].…”
Section: Methodsmentioning
confidence: 99%